Status of Padyak Drivers in Rosary Heights, Cotabato City - Sedik-Salam, Marwisa (Social Sciences and Development Review, 2015)
The purpose of this study was to find out the status of the padyak or pedicab drivers in Rosary Heights 4, Cotabato City. The study utilized both quantitative design which described the socio-demographic profile of the respondents and qualitative design that determined the life experiences, reasons why these respondents engaged into driving padyak and common problems they encountered. An interview guide questionnaire was used to elicit information from the respondents. In the collection of data, purposive sampling technique was employed with the assistance of the barangay chairman and dispatcher who recommended the respondents of the study.